Indicators of Identity and Psychological Well-Being in Immigrant Population - Henríquez, Diego; Urzúa, Alfonso; López-López, Wilson (Frontiers in Psychology, 2021)
Multiple research has indicated that group identity processes are critical to understanding the dynamics of psychological well-being linked to migration. However, few studies have analyzed the relationship between identity from different theoretical perspectives, and the mental health of migrants in the Latin-American context. Therefore, the purpose of this study was to analyze the relationship between several identity indicators such as ethnic identity, collective self-esteem, identity fusion (with the country of origin and the host country) simultaneously, and different dimensions of psychological well-being of Colombian migrants living in Chile. The sample consisted of 887 Colombian migrants, of whom 435 (49%) were men and 452 (51%) were women. Participants were residents of the cities of Arica (n=204; 23%), Antofagasta (n=469; 52.9%), and Santiago (n=214; 24.1%) in Chile. The results revealed by structural equation modeling indicate that collective self-esteem and ethnic identity show positive relationships with almost all dimensions of psychological well-being, while identity fusion with Colombia only showed a positive relationship with the dimension positive relationships and identity fusion with Chile only showed a positive relationship with the dimension autonomy. Implications and limitations of these results are discussed at the end.